Model Pendidikan Karakter Peduli Lingkungan Di Sekolah Penerima Adiwiyata S1 Pendidikan Vokasi Konstruksi Bangunan Fakultas Teknik Universitas Negeri Jakarta - Mita Soraya; Henita Rahmayanti; R Eka Murtinugraha (LPPM Universitas Negeri Jakarta, 2019)
Abstract Research aim is to understand the extent of relevance teaching matter in the studying to become with matter teaches at smk the technical expertise building.Research done to suggest course education building technique engineering faculty jakarta state university in determining teaching matter who would be taught, so teaching matter in learned on a course education building technique engineering faculty jakarta state university relevant to the matter teaches in learn in schools.The research in course education building technique engineering faculty jakarta state university. Time research on november 2017 - december 2017 .Research methodology uses the method descriptive qualitative .Technique data collection used analysis the content and direct interview . The results of the study is showed the value of relevance matter teaching lecture majors in course of study education technique building of engineering faculty jakarta state university with matter teaching in smk program expertise technique building as big as 93,33 % the subjects drawing technique, 88,89 % for the mechanics technique, 91,67 % for the construction of buildings, 100 % for the science of measuring land, to draw interiors and exterior not relevant, 42,11 % to draw the construction of buildings 1 and 2, 81,82 % for construction reinforced concrete, 84,21 % for the construction of masonry, 45,45 % for finishing building, for the implementation of wooden construction, finishing wood and technology wooden construction not relevant. Keywords: relevance 2013 curriculum , teaching matter , the eye studying to become.